2019
DOI: 10.5902/1980509838430
|View full text |Cite
|
Sign up to set email alerts
|

Potential distribution of <i>Ocotea odorifera</i> (Vell.) Rohwer in urban areas of Curitiba, Paraná state, Brazil

Abstract: Potential distribution of Ocotea odorifera (Vell.) Rohwer in urban areas of Curitiba, Paraná state, Brazil Distribuição potencial de Ocotea odorifera (Vell.) Rohwer na área urbana de Curitiba, Paraná, Brasil AbstractOcotea odorifera is an endangered tree species, threatened by the urbanization process that occurs in the region of Curitiba, Paraná state, among other factors. Thus, the knowledge about their geographical distribution becomes necessary to plan protected areas that mitigate the effects caused by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Although this is a common species in the Curitiba region, the potential distribution modeling for A. angustifolia indicated that its occurrence is conditioned by specific landscape factors such as topography and pedology. The presence of species individuals in a given location may not necessarily characterize it as the best environment for its development, since individuals may have adapted to less favorable conditions, even if they do not meet all the autecological demands of the species and therefore do not develop as well as possible [18].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although this is a common species in the Curitiba region, the potential distribution modeling for A. angustifolia indicated that its occurrence is conditioned by specific landscape factors such as topography and pedology. The presence of species individuals in a given location may not necessarily characterize it as the best environment for its development, since individuals may have adapted to less favorable conditions, even if they do not meet all the autecological demands of the species and therefore do not develop as well as possible [18].…”
Section: Discussionmentioning
confidence: 99%
“…This occurrence probability indicated the environmental adequacy for the species' occurrence [17]. A total of 1,000 combinations were established with 10 repetitions in the cross-validated method, and the radius was adjusted to "-30" due to the work scale [18].…”
Section: Methodological Proceduresmentioning
confidence: 99%
See 3 more Smart Citations